If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(v + 3) + 3 + 7v = 0 Reorder the terms: 8(3 + v) + 3 + 7v = 0 (3 * 8 + v * 8) + 3 + 7v = 0 (24 + 8v) + 3 + 7v = 0 Reorder the terms: 24 + 3 + 8v + 7v = 0 Combine like terms: 24 + 3 = 27 27 + 8v + 7v = 0 Combine like terms: 8v + 7v = 15v 27 + 15v = 0 Solving 27 + 15v = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 15v = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 15v = 0 + -27 15v = 0 + -27 Combine like terms: 0 + -27 = -27 15v = -27 Divide each side by '15'. v = -1.8 Simplifying v = -1.8
| m^2(mn)= | | 15x^2+8x-1=0 | | 12.7+.10h=13.5+10h | | 0=-10t^2+12t+54 | | 8m-3-3m=12+2m | | 100+1,000= | | E+2E-2=2E | | 42=8x-6 | | -3(2b-2a)= | | 5x^2+11x=7 | | 4x-60=0 | | -3e+12=5(e+52) | | 2y^3=10y | | 9ln(x+6)-4lnx= | | h=240t-16t^2 | | 7z=13z-12 | | 29x+43=43+27x | | (4x+5)(-2x+8)=0 | | 6x(y-z)= | | 1+2+4= | | 7(x-5)-2x=5(x-6)-5 | | 1=8x^2+7 | | 9p-14=p-47 | | lx-1l-2l=1 | | 14u^2+32u-u^3=0 | | 79(x-5)-2x=5(x-6)-5 | | 5(4x+6)=10(2x-5) | | 0=14u^2+32u-u^3 | | 3p+15=23 | | 1+n/11=9 | | y-5=-9(x-1) | | 6+6x=5x-9x-2 |